POPULATION STRUCTURECerithidea obtusa (GASTROPODS) IN MANGROVE FOREST OF SUNGAI CINGAM VILLAGE RUPAT SUB-DISTRICT OF BENGKALIS REGENCY - Sirait, Jhon Lenon; Nasution, Syafruddin; Tanjung, Afizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Cerithidea obtusa is one species of Mollusc from the family Potamididae which has economic value. This research was conducted in Maret 2018 in mangrove forest the village of Sungai Cingam Rupat Sub-District Bengkalis Regency. This research aimed to determine the populations structure of C. obtusa which cover density, distribution patterns and size distribution. This research used survey method and sampling location determinined by purposive sampling. Measurement of waters quality was done by in situ and ex situ which consists of physical and chemical parameters of the waters. Condition of substrate in the study area was muddy, with sediment organic matter was high 10.69 % -13.95 %. The parameters of waters quality still support for the life of the gastropod. The average density was 5.3 ind/m2, the highest density was in upper zone and which the lowest at middle zone of the intertidal . The distribution patterns was uniform/evenly, while size of the gastropod found has a length 31,8-52,3 mm. Key words: density, size distribution, distribution patterns, C. obtusa.